The Optimal Policies for Restricting Trade under Uncertainty - Young, L.; Anderson, J. E. (Review of Economic Studies, 1980)
Leslie Young, James E. Anderson; The Optimal Policies for Restricting Trade under Uncertainty, The Review of Economic Studies, Volume 47, Issue 5, 1 October 198